The experiences of night shift workers following three different dietary weight loss interventions: a qualitative study using behaviour change theory - Corinne Davis; Sue Kleve; Catherine E. Huggins; Maxine P. Bonham (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Shift workers are an estimated 15%—30% of the workforce in developed countries, who are disproportionally at risk of living with overweight or obesity. Dietary guidance is a component recommended for obesity management, however lacks consideration of the lifestyle and circadian disruption experienced by night shift workers. There is a lack of evidence addressing both weight loss and the metabolic consequences of eating at night. Intermittent fasting (IF) may provide metabolic benefits if fasting is aligned with night shifts. The Shifting Weight using Intermittent Fasting in night shift workers study compares three weight-loss interventions: 1) continuous energy restriction (CER); or twice-per-week IF with 2) fasting during night shifts or 3) day fasting. This study aims to explore the experiences of participants while following the interventions to understand how intervention features and external enablers or barriers influence engagement. Methods Forty-seven semi-structured interviews (22 baseline, 25 follow-up) were conducted with 33 participants. Eighteen participants also completed optional fortnightly audio diaries to enrich data collected on experiences over time. Interviews and diaries were analysed using the five-steps of framework analysis and themes were deductively mapped to behaviour change frameworks and the social-ecological model. Results Analysis resulted in seven major themes and 27 subthemes. Three main themes describe intervention factors influencing engagement: 1) Simplicity and ease, 2) Support and accountability, and 3) An individualised approach is sometimes needed. Four themes described external factors to the interventions influencing engagement: 4) Personal motivation and attitudes, 5) Physiological influences of eating behaviours, 6) Social support at home and work, and 7) Work structure and environment. Conclusions Across all three interventions, participants valued the ease of interventions, which was the clear dietary prescription and focus on two days per week for IF, or a focus on small changes for CER. Behavioural regulation and providing meals/snacks were identified as critical features. Modifications to address identified enablers/barriers include: providing flexible fasting periods; addition of fatigue management initiatives; increased focus on non-weight related health changes during periods of slowed weight-loss; implementation in workplace settings to harness social support; and providing a healthier food environment.